Assessment of natural assets in the agricultural and aquatic ecosystems in Sogod Bay, Southern Leyte - Montes,Humberto R.; Lina, Suzette B.; Patindol, Teofanes A.; Diola, Adelfa C.; Espinosa, Eliza D.; Mazo,Analyn M.; Evangelio, Julissah C.; Flandez,Art Russel R.; Gesultura, Marianne A.; Modina, Ris Menoel R. (EEPSEA research report, 2015)
This study assessed the existing natural resources in Sogod Bay, Southern Leyte, Philippines, and determined how their quality has been affected by the economic activities in the area. Soil physical analysis revealed that some nutrients in the study sites are deficient, particularly phosphorus. A diverse species of mangroves and macroinvertebrates can be found at the study sites. Those with MPAs have good coral covers and high life form diversity indices, while the opposite was observed in non-MPA sites. However, there were also non-MPA sites that exhibited good coral covers and rich species diversity. Results also showed that the natural resources in Sogod Bay are no longer as productive as before due to the decreased quality of these resources. Based on survey results, most households are less dependent on fishery and farming as livelihood sources; most households had nonfarm income sources, which are the largest contributors to household income. Meanwhile, the valuation results indicate that the values of the provisioning services of these ecosystems are higher in sites with MPA and in farms with adequate nutrients and proper cultivation. Hence, this study recommends establishing marine sanctuaries and improving land productivity to restore the marine and terrestrial ecosystems in Sogod Bay.